Gut Microbiota Modulates Obesity‐Associated Skeletal Deterioration Through Macrophage Aging and Grancalcin Secretion - Min Huang; Mei Huang; Ling Liu; Fang Yang; Chen He; Yu‐Chen Sun; Yu‐Rui Jiao; Xiang Tang; Jing Hou; Kai‐Xuan Chen; Wen‐Zhen He; Jie Wei; et al. (Advanced Science, 2025)
Abstract Obesity is associated with skeletal deterioration and increased fracture risk, but the underlying mechanism is unclear. Herein, it is shown that obese gut microbiota promotes skeletal deterioration by inducing bone marrow macrophages (BMMs) senescence and grancalcin (GCA) secretion. Obese mice and those receiving obese fecal microbiota transplants exhibit increased senescent macrophages and elevated GCA expression in the bone marrow. In a study of 40 participants, it is found that obese patients are associated with higher serum GCA levels. It is further revealed that obese gut‐microbiota derived lipopolysaccharides (LPS) stimulate GCA expression in senescent BMMs via activating Toll‐like receptor 4 pathway. Mice with depletion of the Gca gene are resistant to the negative effects of obesity and LPS on bone. Moreover, neutralizing antibody against GCA mitigates skeletal deterioration in obese mice and LPS‐induced chronic inflammation mouse model. The data suggest that the interaction between gut microbiota and the immune system contributes to obesity‐associated skeletal deterioration, and targeting senescent macrophages and GCA shows potential of protecting skeletal health in obese population.